Adsorption and transformations of ethene on hydrogenated rhodium clusters in faujasite-type zeolite. A computational study. Issue 6 (28th October 2015) - Markova, Velina K.; Vayssilov, Georgi N.; Genest, Alexander; Rösch, Notker
Abstract : Phase diagrams from DFT modeling suggest that zeolite-supported Rh4 clusters may be appropriate for the catalytic hydrogenation of ethene to ethane, whereas Rh3 clusters favor the formation of the stable adsorbed ethylidyne species, preventing further hydrogenation. Abstract : Regarding the heterogeneous catalytic hydrogenation of ethene on small rhodium clusters, anchored in faujasite, we computationally studied C2 H x ( x = 2–5) intermediates on zeolite-supported Rh3 and Rh4 clusters with pre-loaded hydrogen. According to the calculated Gibbs free energies, at temperatures and hydrogen pressure values representing pertinent experiments, the favored stable species on hydrogen-loaded Rh3 is ethylidyne which apparently prevents further hydrogenation due to its strong CH3 –CRh n interaction. In contrast, on bare and hydrogenated Rh4 clusters, the partially hydrogenated species C2 H5, a locally stable intermediate, is among the most stable adsorption complexes examined. These "pseudo ethyl" C2 H5 ligands exhibit a very specific structure, where both carbon atoms and a hydrogen atom of the organic moiety interact with the apical Rh center of Rh4 ; previously, such ligand structures have been identified only computationally as transition states in homogeneous catalysis of ethene hydrogenation. According to our analysis based on the thermodynamic phase diagrams, one is led to conclude that only Rh clusters of such specific topology may be appropriate for the catalytic hydrogenation of ethene, in contrast to the zeolite-supported Rh3 clusters. Suggestions are made for further probing this size-specific catalytic activity of Rh clusters.